2021
DOI: 10.1038/s41416-020-01226-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of interferon-signalling halts cancer-associated fibroblast-dependent protection of breast cancer cells from chemotherapy

Abstract: This is a repository copy of Inhibition of interferon-signalling halts cancer-associated fibroblast-dependent protection of breast cancer cells from chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 46 publications
0
28
3
Order By: Relevance
“…Absorbance was assessed at 570 nm using a Mithras LB940 plate reader (Berthold; Bad Wildbad, Germany). Clonogenic survival assays were performed as described previously [ 24 ]. In brief, cells were transfected, treated with epirubicin, and reseeded at low density (100 MCF7 or 200 MDA-MB-175 cells per well of 6-well plates) in technical duplicates without further epirubicin.…”
Section: Methodsmentioning
confidence: 99%
“…Absorbance was assessed at 570 nm using a Mithras LB940 plate reader (Berthold; Bad Wildbad, Germany). Clonogenic survival assays were performed as described previously [ 24 ]. In brief, cells were transfected, treated with epirubicin, and reseeded at low density (100 MCF7 or 200 MDA-MB-175 cells per well of 6-well plates) in technical duplicates without further epirubicin.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of the type I IFNs (IFN-α/β) signaling pathway can cause cancer cell apoptosis and cellular senescence, and breast tumor cell secreted type I IFNs has been shown to induce anti-metastatic response. However, type I IFNs also attributed to drug resistance specifically in triple negative breast cancers (TNBC) and inflammatory breast cancer (IBC) ( 56 , 57 ). Type II IFNs (IFN-γ), on the other hand, has been reported to cause tissue damage in response to tumor hyperproliferation.…”
Section: Preclinical Studies Targeting Innate Immunity For Breast Cancer Therapymentioning
confidence: 99%
“…Furthermore, independent prognostic factors were used to construct a nomogram to directly predict individual OS based on six CAFs-related-gene signature risk score (Figure 5). It was revealed that the main enriched pathways in the tumor, including epithelial-mesenchymal transformation (Shintani et al, 2016), hypoxia (Lappano et al, 2020), inflammatory Response (Ershaid et al, 2019), interferon-gamma response (Broad et al, 2021), and NFkB-mediated TNFα signal transduction (Katanov et al, 2015) were closely related to the function of CAFs. These observations indicate that risk scores can fully reflect the function of CAFs (Figure 6A).…”
Section: Discussionmentioning
confidence: 99%